Particleboard manufacturing : a pre-feasibility study (E R Broughton Associates TorontoCA, 1982)
Discusses development and characteristics of particleboard. Reviews the CARICOM situation highlighting constraints to viable production of particleboard and outlining conditions in several CARICOM Member States which are suitable for manufacture of particleboard. Assesses market potential for particleboard in the CARICOM Region. Discusses most suitable type of plant for the Region, various location options, raw materials required, technical features of the plants, and labour force needed. Outlines project scheduling for Couva plant modification and for the construction of a new plant in either Guyana or Belize. Gives three financial analyses for three plants based on different production options.
IDS